Peranan Endorse “Walls” Terhadap Keputusan Pembelian - Stefani Stefani; Delong Gunawan; Josephine Artanto; Pradana Sinaga; Manisa Manisa (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
The study investigates how the "Walls" brand influences consumer purchasing decisions. After the data was collected and analyzed using a regression model, the research investigated the significance of the value of the coefficient and the SIG. The research found that the meaningful value was 7,908, and SIG was below the limit of significance 0.05. This suggests that "Walls" support has a significant impact on customers' choices about what they buy. However, to understand more deeply how "Wells" support directly affects purchasing decisions, more information is needed.